2014
DOI: 10.5210/fm.v19i3.5227
|View full text |Cite
|
Sign up to set email alerts
|

Taking tweets to the streets: A spatial analysis of the Vinegar Protests in Brazil

Abstract: In this paper we investigate the relationship between the geographic location of protestors attending demonstrations in the 2013 Vinegar protests in Brazil and the geographic location of users that tweeted the protests. We explored the overlap between different sources of geographic information from Twitter -namely geocode, hashtag, and user profileprovided by multiple samples drawn from a population of three million tweets related to the events and compared the data to the location of protestors attending the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 35 publications
0
28
0
6
Order By: Relevance
“…It stems from the way in which the dominance of big data analytics as an emerging set of quantitative methodologies in the social sciences has marginalized the study of symbolic processes whose understanding requires the nuanced and in-depth discernment of qualitative methods (boyd & Crawford, 2012;Couldry, 2014). Big data analysis has become a scholarly 'fashion' among researchers looking at the wave of recent protest movements: on the Occupy movement (Conover et al, 2013;Gaby & Caren, 2012), on the Arab Spring (Starbird & Palen, 2012), the Brazilian vinegar protests (Bastos, Da Cunha Recuero, & da Silva Zago, 2014), the 15M/Indignados Spanish movement (Toret et al, 2015), and the Aganaktismenoi in Greece (Theocharis, Lowe, van Deth, & García-Albacete, 2015). While this stream of analysis has considerable merits, data analysis alone is not always well suited to get to grips with symbolic processes and the construction of collective identity.…”
Section: Introductionmentioning
confidence: 99%
“…It stems from the way in which the dominance of big data analytics as an emerging set of quantitative methodologies in the social sciences has marginalized the study of symbolic processes whose understanding requires the nuanced and in-depth discernment of qualitative methods (boyd & Crawford, 2012;Couldry, 2014). Big data analysis has become a scholarly 'fashion' among researchers looking at the wave of recent protest movements: on the Occupy movement (Conover et al, 2013;Gaby & Caren, 2012), on the Arab Spring (Starbird & Palen, 2012), the Brazilian vinegar protests (Bastos, Da Cunha Recuero, & da Silva Zago, 2014), the 15M/Indignados Spanish movement (Toret et al, 2015), and the Aganaktismenoi in Greece (Theocharis, Lowe, van Deth, & García-Albacete, 2015). While this stream of analysis has considerable merits, data analysis alone is not always well suited to get to grips with symbolic processes and the construction of collective identity.…”
Section: Introductionmentioning
confidence: 99%
“…I performed several complexity reduction operations on the data, which involved first removing all isolated nodes from the analysis and then retrieving the concepts in the data pertaining to protest locales outside Romania (for example London or Berlin). Researchers consider this method of pinpointing protest localities more reliable than the geocode information attached to social media data (Bastos et al 2014); and, crucially, it was in line with my aim expounded below to probe associative frames connecting location with identity and organizational concepts.…”
Section: Methodsmentioning
confidence: 69%
“…Indeed, Juris (2012: 260) suggested that the Occupy Movement embraced social media for the rapid, scalable though ultimately transient aggregation of masses of individual actors. Nonetheless, contextual factors such as entrenched geodemographic divisions in a country, or the political and socio-economic prominence of a protest locality, which might range from socio-economic centres to remote rural areas (Bastos et al 2014), circumscribe the use of social media in a protest.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A escolha dos veículos da imprensa foi realizada tendo por base estudos anteriores sobre o mesmo evento no mesmo período (Bastos, Recuero & Zago, 2014). Inicialmente foram selecionadas no Twitter 10 contas de veículos jornalísticos brasileiros mais citados de um conjunto de mais de um milhão de tweets.…”
Section: Coleta De Dadosunclassified